PSYCHOLOGICAL EFFECTS OF SECOND WAVE FEMINISM THROUGH THE LENS OF COGNITIVE LINGUISTICS - AL-JANABI, SUADAD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Women's rights have sparked support and opposition, with antifeminist rhetoric challenging feminism's impact on families and gender roles. Janice Fiamengo's 2018 book Sons of Feminism: Men Have Their Say consists of 25 stories by men narrating their experiences in a feminist society. In this study, five stories related to the second wave of feminism were selected as the data for analysis. Conceptual Metaphor Theory and Conceptual Blending are cognitive tools used in the analysis. The study examines how feminism affects men psychologically by instilling fear and punishing dissent through metaphors that evoke feelings of oppression, fear, and emotional distress. The study concludes that fear, terror, and humiliation evoke psychological stress as an ongoing state under feminist surveillance, instantiating a culture of submission that prevents open speech, diminishes male agency, constrains freedom, and instantiates a discourse in which males must comply to avoid professional ruin and family estrangement.